IS CHINA A THREAT TO INDONESIA: A DISCOURSE ANALYSIS OF MAJOR INDONESIAN NEWSPAPERS’ COVERAGE ON THE CHINA ISSUES - Rizki Hegia Sampurna (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This study aims to find out how China's threat narratives are represented in the potrayal of Chinese issues in major Indonesian newspapers. The study found that some elements or themes of the Chinese threat theory are represented in four Indonesian major newspapers namely Republika, Jawa Pos, Jakarta Pos and Kompas. Mainland Chinese workers, infrastructure projects under China, and transnational drug trafficking appeared as the frequent themes of the China threat in these newspapers. However, the four newspapers were divided and took different public attitudes about the Chinese threat narrative. On the one hand, Republika and Jawa Pos tend to take the public side and are more inclined towards echoing Chinese threat narrative. On the other hand, the Jakarta Post and Kompas seem to take a government stance and neutralize the China issues from the threat narrative.